Cho 10 a 2 = 10 b 2 + c 2 . Chứng minh rằng ( 7 a − 3 b + 2 c ) ( 7 a − 3 b − 2 c ) = ( 3 a − 7 b ) 2
Cho 10a2=10b2+c2. Chứng minh rằng (7a−3b+2c)(7a−3b−2c)=(3a−7b)2
RR
R. Roboctvx92
Giáo viên
Xác nhận câu trả lời
Giải thích
Ta có: V T = ( 7 a − 3 b + 2 c ) ( 7 a − 3 b − 2 c )
= ( 7 a − 3 b ) 2 − ( 2 c ) 2 = 49 a 2 − 42 ab + 9 b 2 − 4 c 2
Từ 10 a 2 = 10 b 2 + c 2 ⇒ c 2 = 10 a 2 − 10 b 2
Suy ra V T = 49 a 2 − 42 ab + 9 b 2 − 4 ( 10 a 2 − 10 b 2 )
= 9 a 2 − 42 ab + 49 b 2 = ( 3 a − 7 b ) 2 = V P ( đ p c m )